Особливості функціонування сучасного студентського самоврядування в Україні та країнах Європи - Бірюкова, Марина Василівна (НТУ "ХПІ", 2017)
У статті досліджуються специфіка становлення студентського самоврядування в період розбудови незалежної України. Особливу увагу приділяється функціям, що надається студентському самоврядуванню у вищих навчальних закладах України. Для виявлення особливостей сучасного стану розвитку студентського самоврядування проведено порівняльний аналіз функціонування цього соціального інституту в інших країнах Європи. Визначено проблемні аспекти функціонування сучасного інституту самоврядування у ВНЗ України.

The article investigates the specifics of the formation of student government in the period of the development of independent Ukraine. Particular attention is paid to the functions that ensure student self-government in higher educational institutions of Ukraine. A comparative analysis of the functioning of this social institution in other European countries was carried out to reveal the features of the current state of development of student self-government. The problem aspects of the functioning of the modern institute of self-government in universities of Ukraine are determined.
Features of the functioning of modern student self-government in Ukraine and European countries
Keywords: вищий навчальний заклад; система освіти; школа вища; законодавство; higher education institution; student; self-government